Survival and time interval from surgery to the start of chemotherapy for patients with stage II and III colon cancer - Ganenko, Denis; Dulskas, Audrius; Kuliešius, Žygimantas; Baltruškevičienė, Edita; Urbonas, Vincas; Stratilatovas, Eugenijus (Acta medica Lituanica, 2019)
Background. Usually adjuvant chemotherapy is started within 12 weeks of surgery, but the evidence on the commencing time is lacking. Our aim was to investigate the association of initiating post-surgery treatment within six weeks vs. six to ten weeks vs. more than ten weeks with survival. Methods. We analysed the association of treatment and its timing with survival among patients who were diagnosed and underwent surgery for stage II or III colon cancer from 2012 to 2013 at the National Cancer Institute, Lithuania. Results. Of the 86 patients, 78% were still alive on December 31, 2013. Patients who received chemotherapy within six weeks after surgery were more likely to survive. However, those who received chemotherapy 6–10 weeks after surgery had better survival (p – 0.014, hazard ratio 0.80, 95% CI 0.60–0.99) than those who began chemotherapy treatment more than ten weeks after surgery (p – 0.173 hazard ratio 0.55, 95% CI 0.12–0.99) Conclusions. The results from this study show that optimal timing of adjuvant chemotherapy for patients with resected colon cancer within six weeks and associated with better survival.